2020
DOI: 10.1161/str.51.suppl_1.85
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 85: Periodontal Disease Association With Large-Artery Atherothrombotic Stroke

Abstract: Introduction: Periodontal disease (PD) is associated with incident and recurrent ischemic stroke. We investigated whether PD is associated with specific stroke subtype. Methods: In this cross-sectional study, PD was assessed in ischemic stroke and TIA patients. Moderate-severe PD was determined by full-mouth examination by a dentist. Clinical information including stroke etiological subtype (TOAST) was collected at admission. Based on vascular imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…15 The selection bias was also detected in the study by Leira et al, along with a lack of validity of the patient history, which was assessed by interviewing the participants. 19 The selection bias was also observed in the study by Mascari et al 22 A small sample size was observed in the study by Sen et al 17 Six studies explored the association between GI and stroke. One study was an original study, 2 studies were cohort, and 3 were case-control studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…15 The selection bias was also detected in the study by Leira et al, along with a lack of validity of the patient history, which was assessed by interviewing the participants. 19 The selection bias was also observed in the study by Mascari et al 22 A small sample size was observed in the study by Sen et al 17 Six studies explored the association between GI and stroke. One study was an original study, 2 studies were cohort, and 3 were case-control studies.…”
Section: Discussionmentioning
confidence: 92%
“…) Methodological quality of the included studies (cohort and cross-sectional studies11,12,14,17,[20][21][22][23] …”
mentioning
confidence: 99%